Evolution of morphology and of chemical conversion along the screw in a corotating twin-screw extruder - Machado, A. V. (1999)
A new sampling device is used to perform near-real-time investigations of physical and chemical processes occurring inside a laboratory twin-screw extruder. Polyamide-6-ethylene propylene rubber (PA-6-EPM) blending and styrene-maleic anhydride (SMA) imidation experiments are reported in terms of morphology development and evolution of the chemical conversion along the extruder, respectively. Comparison of the results obtained using this new technique with those of classical screw-pulling experiments evidenced the potential erroneous conclusions than can be drawn from the latter.